Organisational culture and coach-athlete relationships: An ethnographic study of an elite rowing club - Maitland, A. (2012)
This thesis explores how coach-athlete relationships are influenced within the organisational culture of a rowing club. Relational Cultural Theory and the work of Weber are used to examine how the concept of organisational culture informs understanding of coach and athlete relating. The study, covering a complete competitive season, involved an eleven month long ethnography of an elite rowing club in Great Britain. The findings demonstrate the visceral, enculturated and complex nature of coach-athlete relationships in elite sport. Relational disconnection occurred in the disenchanted organisational life, where intrinsic values were subordinated to a rational quest for efficiency, control and ultimately success, as well as traditional social ordering based on status and gender. Relationships were characterised by power over relating, distance and impersonal relations, caretaking rather than caring about, fragile trust by the athlete and trust through surveillance by the coach, where emotion was concealed and conflict avoided. However, enacting shared identities, the emotion involved in competing and the fact this was a voluntary organisation with competing values, provided an escape from simulacra of elite sport to allow for multi-value paradigm of interests. The opportunity for coaches and athletes to connect with each other based on their values and with emotion exposed their humanity and revealed the potential for relational mutuality and authenticity. The study challenges the valorised coaching and elite sport relationships and lifestyle. Implications for coaching include providing individuals with confidence to raise the issue of relationship, providing coaches and athletes with knowledge of connection and disconnection in relationship and the outcome on well-being. The need to develop a systemised approach to embedding growth-fostering relationships in the culture of high performance sport is highlighted.